-2(3s-1)-2=2(5s+3)-3

Simple and best practice solution for -2(3s-1)-2=2(5s+3)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3s-1)-2=2(5s+3)-3 equation:


Simplifying
-2(3s + -1) + -2 = 2(5s + 3) + -3

Reorder the terms:
-2(-1 + 3s) + -2 = 2(5s + 3) + -3
(-1 * -2 + 3s * -2) + -2 = 2(5s + 3) + -3
(2 + -6s) + -2 = 2(5s + 3) + -3

Reorder the terms:
2 + -2 + -6s = 2(5s + 3) + -3

Combine like terms: 2 + -2 = 0
0 + -6s = 2(5s + 3) + -3
-6s = 2(5s + 3) + -3

Reorder the terms:
-6s = 2(3 + 5s) + -3
-6s = (3 * 2 + 5s * 2) + -3
-6s = (6 + 10s) + -3

Reorder the terms:
-6s = 6 + -3 + 10s

Combine like terms: 6 + -3 = 3
-6s = 3 + 10s

Solving
-6s = 3 + 10s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-10s' to each side of the equation.
-6s + -10s = 3 + 10s + -10s

Combine like terms: -6s + -10s = -16s
-16s = 3 + 10s + -10s

Combine like terms: 10s + -10s = 0
-16s = 3 + 0
-16s = 3

Divide each side by '-16'.
s = -0.1875

Simplifying
s = -0.1875

See similar equations:

| w/7-4=13 | | 3x+1.5y+1.5z=204 | | 3+.75x=10+.50x | | X/-2-1=12 | | 8+4x=x+38 | | 5-q=-q-4 | | y=1/2x-8(-6,-17) | | 18/c=-28 | | 150/2=x | | 2-7x=14-9x | | 0=5x^2-11x+2 | | 4k-9=7k | | 30*5=x | | a^4+a^3-9a^2-9a= | | h/2x2/h | | 5r-6=1r+3 | | z=4x-4 | | 0=7h^2+10h+3 | | 7/5x | | 5x+47=-1-3x | | 2x+3x+5=50 | | a+54=180-2a | | 4k-9=7k | | 7-2x=2-4 | | (x^-2/4x^-6)^-2 | | 3x-9/40 | | 1-4k-2=-8k | | 7+-8c-48= | | 7(2x-10)-(5-7x)= | | h1/3-4=13 | | 16m^4-25m^2+9= | | 30/4.10 |

Equations solver categories